Multiple Lytic Bone Lesions Mimicking Langerhans Cell Histiocytosis: A Case of Infantile Mendelian Susceptibility to Mycobacterial Disease due to STAT1 Deficiency. (11th October 2022) - He, Yingyi; Zhang, Hui; Li, Chunjie; Su, Xiaoling; Gan, Wenting; Wang, Pengfei; Xiao, Weiqiang
Abstract: We present the first infantile disseminated Bacillus Calmette-Guérin (BCG) disease case with STAT1 deficiency, which is manifested by multiple Langerhans cell histiocytosis–like osteolytic lesions. The diagnosis of BCG-induced osteomyelitis was not initially considered until the additional biopsy revealing granulomatous inflammation, a key pathological diagnostic component for mycobacterial infection.